Currency Crisis and Contagion : Evidence From Exchange Rates and Sectoral Stock Indices of the Philippines and Thailand - Nagayasu, Jun (IMF Working Papers; Working Paper, 2000)
This paper analyzes empirically the recent Asian financial crisis using high frequency data of exchange rates and stock indices of the Philippines and Thailand. Utilizing standard time-series techniques, this study confirms that there is evidence that developments in some sectoral indices-including those of banking and financial sectors-seem to have caused upward pressure on exchange rates. A correlation between some of these variables is also found to be strong across countries in the crisis period, thereby confirming the importance of the linkages between financial markets as a transmission channel of the Thai crisis to the Philippines.